Objective Structured Clinical Examinations practices across Canadian medical schools: a national overview - Chris Gilchrist; Zia Bismilla (Canadian Medical Education Journal)
Introduction: Objective Structured Clinical Examinations (OSCEs) are crucial in assessing clinical competencies, but their implementation varies widely across medical schools. This work examines OSCE practices across Canadian medical schools, focusing on frequency, type, and timing.